Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It has been a while since I have done any maths and am struggling with this question -

Using the addition law $$\sin(A+B) = \sin(A)\cos(B) + \cos(A)\sin(B)$$ and the fact that $\sin(-\theta) = -\sin(\theta)$ and $\cos(-\theta) = \cos(\theta)$, show that $$\sin(A-B) = \sin(A)\cos(B) - \cos(A)\sin(B)$$

I am really confused as to where to even start, so any help is appreciated!!

share|cite|improve this question
Hint: Substitute $-B$ into your expression for sin(A+B) and use the identities. – Amzoti Mar 6 '13 at 4:27
Let $C=-B$. Then $\sin(A-B)=\sin(A+C)$. See if you can take it from there. – crf Mar 6 '13 at 4:28

Hint: $$\quad A-B=A+(-B)\quad $$

share|cite|improve this answer

There's hardly anything to do: \begin{align} \sin(A-B) & = \sin(A+(-B)) = \sin A\cos(-B) + \cos A \sin(-B) \\[6pt] & = \sin A\cos B + (\cos A)(-\sin B) \end{align} followed by one trivial step.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.